Ulul Albab–Based Lesson Study in Madrasah Aliyah: A School Action Research on Science and Mathematics Teachers’ Pedagogical Transformation - Indri Indri; Anniez Rachmawati Musslifah; Harun Joko Prayitno; Sofyan Anif; Mazlini Adnan (Nazhruna: Jurnal Pendidikan Islam, 2026)
The integration of Islamic values into science and mathematics instruction in madrasahs remains a persistent challenge in Classroom practice. While prior studies on Lesson Study have demonstrated improvements in instructional quality and collaborative reflection, limited attention has been given to how such professional learning structures can support the enactment of value-based pedagogies. This study addresses that gap by examining a modified Lesson Study model grounded in the Ulul Albab framework within a school-based action research design conducted over two cycles at a Madrasah Aliyah in Indonesia. Data were collected through participatory observation, in-depth interviews, and lesson plan analysis. The findings indicate that the model contributed to measurable shifts in teachers' pedagogical practices, particularly in the design of inquiry-based lessons that integrated reflective and ethical dimensions alongside scientific reasoning. However, the integration process was not uniform; some teachers initially reverted to symbolic or add-on approaches before gradually developing more coherent alignment between content and values. Compared to conventional Lesson Study implementations, the Ulul Albab-based model explicitly structures reflective dialogue around the epistemic and ethical dimensions of the subject matter, thereby extending the scope of collaborative inquiry beyond pedagogical techniques. These findings suggest that Lesson Study can function not only as a mechanism for improving instructional strategies but also as a structured space for negotiating the pedagogical meaning of value integration. The study contributes an empirically grounded professional development model that demonstrates both the possibilities and the practical challenges of translating faith-science integration into Classroom practice.